REPRODUCTIVE PROFILE OF FISH AT SERAYU RIVER IN BANYUMAS - Susanto Susanto; H Suwarno (Universitas Muhammadiyah Purwokerto, 2018)
The purpose of this study is to reveal and describe the growth pattern and profile of fish reproduction and water quality at Serayu River in Banyumas District. This research was conducted using survey method with purposive random sampling technique. The research was conducted in three research locations, each study location was determined by three research stations, and each research station was determined by three sampling points. Fish sampling using fishing nets and hand web, conducted 10 times sampling for each tool at each sampling point. Fish from sampling results were identified by key identification of fish according to Saanin (1968; 1984); Kottelat et al., (1993) and verified at Pusat Penelitian Biologi Lembaga Ilmu Pengetahuan Indonesia (LBN-LIPI) Cibinong and www. FishBase. org. Analysis of condition factor, fecundity, maturity level of gonad, gonad maturity index, and sex ratio based on Susanto (2015); Lagler et al. (1977), and Effendie (1979). Based on the results and discussion, it can be concluded: (1) The quality of waters including physical and chemical parameters of waters, namely: temperature, current velocity, water brightness, dissolved oxygen content and pH and variation of plankton species at Serayu River in Banyumas District are in good condition and suitable for fish life. (2) Reproductive profile of fish at Serayu River in Banyumas District is not ideal.